The Early Iron Metallurgy of Bassar, Togo: furnaces, metallurgical remains and iron objects. Issue 1 (2nd January 2020) - de Barros, Philip L.; Iles, Louise; Frame, Lesley D.; Killick, David
ABSTRACT: An extensive iron production industry flourished in the Bassar region of northern Togo from as early as the Early Iron Age. However, it was during the Later Iron Age that this witnessed a period of rapid growth, with locally produced iron increasingly feeding into regional trade networks. This paper discusses the archaeology, archaeometallurgy and metallography of the earliest iron production in Bassar through the examination of two sites. The first, BAS-252 (Dekpassanware), is a large ironworking village (in operation throughout the Early and Later Iron Ages) with six zones devoted primarily to smithing. The second, the nearby site of BAS-273, was found to be a smaller smelting site and operated in the Early Iron Age. The paper presents a metallographic analysis of the EIA iron artefacts excavated at BAS-252, in conjunction with an archaeometallurgical analysis of EIA smelting remains from BAS-273. The close association of smithing and smelting sites has provided an unparalleled opportunity to consider the chaîne opératoire of iron production in EIA Bassar, with insights into the production of iron alloyed with carbon and phosphorus and the possible symbolic behaviours of past smelters at a time when the foundations were being laid for Bassar to develop subsequently into a regional hub of iron production.